Electrical and mechanical effects of hyoscine butylbromide on the human stomach: a non-invasive approach - Americo, Madileine F. [UNESP]; Miranda, Jose Ricardo A. [UNESP]; Cora, Luciana A. [UNESP]; Romeiro, Fernando G. [UNESP] (Iop Publishing Ltd, 2009)
Due to the importance of motility in a number of gastrointestinal disorders, efforts have been made to evaluate both gastric motility counterparts: electrical activity and mechanical activity. The present work aimed to propose a new approach, associating AC biosusceptometry (ACB) and electrogastrography (EGG), to noninvasively monitoring mechanical and electrical gastric activity, respectively. Fourteen volunteers ingested a test meal and their gastric activity was evaluated by EGG and ACB at a baseline and after 20 mg of i.v. hyoscine butylbromide. ACB and EGG showed a similar signal pattern and high temporal correlation. Hyoscine butylbromide decreased the mechanical motility index (MI) by 50.9%, while for electrical MI the reduction was 36.5%. Delayed times to onset (mean +/- SD: 50 +/- 15 versus 40 +/- 20 s; P < 0.01) and the inhibitory effect (16 +/- 4 versus 14 +/- 5 min; P < 0.01) were calculated for ACB and EGG, respectively. ACB and EGG emerged due to their interesting nature, noninvasiveness and low cost to evaluate gastric motility. Our approach associating ACB and EGG allowed monitoring and quantification of the effects of an anticholinergic drug in gastric electrical activity and contractile activity in humans.
Keywords: hyoscine N-butylbromide; stomach; diagnostic techniques and procedure; humans; drug therapy